The Importance of Nature Exposure and Physical Activity for Psychological Health and Stress Perception: Evidence From the First Lockdown Period During the Coronavirus Pandemic 2020 in France and Germany - Javelle, Florian; Laborde, Sylvain; Hosang, Thomas Jean; Metcalfe, Alan James; Zimmer, Philipp (Frontiers in Psychology, 2021)
Objective: This cross-sectional questionnaire-based study aims to compare physical activity and nature exposure levels between people living in France and Germany during the lockdown. Furthermore, the secondary aim is to observe the relationship between perceived stress, psychological health, physical activity, and nature exposure in Germany and France during the coronavirus disease 2019 (COVID-19)-related lockdown of April/May 2020. Methods: The study includes 419 participants who have completed the Perceived Stress Scale 10, the World Health Organization Quality of Life-BREF, the Godin-Shephard Leisure-Time Physical Activity Questionnaire, the modified Nature Exposure Scale, and complementary questions related to the lockdown period from April 19 to May 11, 2020. Multiple regression models were constructed to evaluate the relationship of nature exposure and physical exercise with overall stress perception and psychological health in France and Germany when considering a broad range of covariates. Results: Exposure to nature during the lockdown (ηp2 = 0.034, p < 0.001), amount of physical activity ηp2 = 0.014, p < 0.001), and psychological health (ηp2 = 0.041, p < 0.001) were greater in German compared with French participants. Godin Index and Nature Exposure Scale total score were both inversely correlated to stress perception and positively correlated to psychological health. The stress and psychological health regression models explained 10% of the results' variance. Physical activity (Godin Index) was a significant for both models. Nature Exposure Scale total score was a significant predictor only for psychological health. When including all significant covariates, the regression models explained 30.7% for the perceived stress and 42.1% for the psychological health total overall variance. Conclusion: Physical activity and nature exposure are significant predictors of psychological health. Even though both variables are associated with stress perception, only physical activity is a significant predictor of stress perception. Our results suggest that physical activity and nature exposure were key factors to go through the lockdown period in France and Germany.